Identification method of structural defects in glass fiber fabric/epoxy resin laminate - Naceri, A. (Проблемы прочности, 2009)
We present the experimental methods proposed for the identification of structural defects of the laminate constituted of 12 layers of glass fiber fabric/epoxy resin. Two techniques of control were used to analyze the principal structural defects (local or global disorientation). The first technique provides a superficial observation (macroscopic analysis) of the superior and lower surfaces of each layer, while the second one ensures internal observation (microscopic analysis) of the different layers after pyrolysis of the matrix (delamination of the laminate). Описано експериментальні методи для ідентифікації структурних дефектів у 12-шаровому ламінаті на основі скловолокнистої тканини й епоксидної смоли. Для аналізу основних структурних дефектів (локальна або глобальна дезорієнтація) використовували два методи. Один метод забезпечує дослідження (макроаналіз) верхньої і нижньої поверхней кожного шару, інший - внутрішнє дослідження (мікроаналіз) кожного шару після піролізу матриці (деламінації ламінату). Описаны экспериментальные методы для идентификации структурных дефектов в 12-слойном ламинате на основе стекловолокнистой ткани и эпоксидной смолы. Для анализа основных структурных дефектов (локальная или глобальная дезориентация) использовались два метода. Один метод обеспечивает исследование (макроанализ) верхней и нижней поверхностей каждого слоя, другой - внутреннее исследование (микроанализ) каждого слоя после пиролиза матрицы (деламинации ламината).